2015
DOI: 10.1111/cup.12546
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of cytokeratin 15, TDAG51, cytokeratin 20 and androgen receptor in sclerosing adnexal neoplasms and variants of basal cell carcinoma

Abstract: Combination of CK20 and AR best differentiated these sclerosing adnexal neoplasms. Greater positivity for CK15 and TDAG51 generally favors benign lesions. Infundibulocystic BCC has higher CK20 and lower AR immunopositivity than other BCC variants and a high degree of CK15 and TDAG51 positivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 26 publications
2
42
1
1
Order By: Relevance
“…CK20 can be used in combination with androgen receptor (AR), with positive tumor AR staining and absent CK20 staining supporting BCC, whereas CK20 þ colonizing Merkel cells and lack of AR support a benign diagnosis. [54][55][56] Several limitations of the AR/CK20 panel should be kept in mind. The AR expression is often focal and sometimes completely absent in BCC.…”
Section: Benign Hair-germ Tumors (Trichoepithelioma Andmentioning
confidence: 99%
See 1 more Smart Citation
“…CK20 can be used in combination with androgen receptor (AR), with positive tumor AR staining and absent CK20 staining supporting BCC, whereas CK20 þ colonizing Merkel cells and lack of AR support a benign diagnosis. [54][55][56] Several limitations of the AR/CK20 panel should be kept in mind. The AR expression is often focal and sometimes completely absent in BCC.…”
Section: Benign Hair-germ Tumors (Trichoepithelioma Andmentioning
confidence: 99%
“…61,64,68,69 Although p75NTR is more likely to show diffuse expression in DTE than in mBCC, 70 a later study 71 demonstrated limited specificity, with diffuse expression in 36% of mBCC and 44% of microcystic adnexal carcinomas. In recent studies, strong and diffuse expression of PHLDA1 (TDAG51), a follicular stem-cell marker, has been shown to be highly specific for TE/TB, 53,55,72 although expression in micronodular BCC has been reported. 72 In summary, although markers, including AR, CK20, and PHLDA1, may be useful in distinguishing BCC from benign, hair-germ tumors, no single marker appears completely sensitive or specific for this distinction.…”
Section: Benign Hair-germ Tumors (Trichoepithelioma Andmentioning
confidence: 99%
“…21 Even cases of infundibulocystic BCC show the same pattern of focal staining for ARs. 21 This is in contrast to the expression of ARs by sebaceous tumors, which is usually seen in >25% of the tumoral cells.…”
Section: Discussionmentioning
confidence: 97%
“…18 Interestingly, most of the structures of the normal follicle are AR negative, and this is also probably why most adnexal tumors showing follicular differentiation are also AR negative, such as pilomatrixomas, 19 trichoadenomas, 20 or desmoplastic trichoepitheliomas. 20,21 Focal immunoexpression of AR has been described in BCC, 2 usually limited to <25% of the cells in most of the cases tested. 21 Even cases of infundibulocystic BCC show the same pattern of focal staining for ARs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation